Pendampingan Manajemen Dan Administrasi Keuangan Pada Koperasi Wanita Arwana Kota Bengkulu - Budi Astuti; Nensi Yuniarti.Zs; Ahmad Sumarlan; Rina Yuniarti; Dwi Okta Nurkhofifah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
The Women's Cooperative "Arwana" which is a legal entity No.: 99/BH/DK PPKM/KEP/IX.4/2008 is a savings and loan cooperative having its address at Jl. Wren Rt. 17/Rw.06 Cempaka Permai Village, Gading Cempaka District, Bengkulu City. This cooperative was established by notarial deed SK. Minister of Law and Human Rights of the Republic of Indonesia Number: C-226.HT.03.01. July 5, 2006 and started operating in 2008. In 2019 this cooperative began to turn into a sharia-based cooperative. This community service activity aims to provide understanding assistance to administrators and members in terms of management as an effort towards better management from conventional to Sharia. So it is hoped that later the management and members of the cooperative in carrying out their duties and responsibilities in accordance with the principles and rules of management can become a financing system in accordance with the sharia concept. This community service is carried out with lectures on the principles of cooperative management. The output of this community service activity is that the management and members of the cooperative, especially in the savings and loan business, are able to know and understand and implement financing business activities with a management system according to SAK ETAP as a step towards developing a financing business that is still using the conventional system to be more ready to use the system. Sharia. The output of this community service is in the form of a scientific journal that will be published.